Mechanism of Chemotherapy Resistance: a Comprehensive Review - Paudel, Subash; Parajuli, Laxmi; Shrestha, Santosh; Rai, Indira (Nepalese Journal of Cancer, 2025)
Chemotherapy resistance is a critical barrier to effective cancer treatment, contributing to the high number of cancers related death in patients. This review comprehensively examines the molecular mechanisms driving resistance, including innate and acquired resistance, tumor heterogeneity, and tumor microenvironment (TME) interactions. Key mechanisms include enhanced drug efflux via ABC transporters, increased DNA repair, altered drug targets, drug detoxification, and evasion of apoptosis. Tumor heterogeneity fosters resistant subclones, while TME factors like hypoxia and cancer-associated fibroblasts (CAFs) exacerbate resistance. Crosstalk between signaling pathways, such as PI3K/AKT and MAPK, fuels resistance but offers hope for combination therapies. Insights into these mechanisms are vital for developing targeted therapies to overcome resistance and improve patient outcomes.